NEGOSIASI ATAS ADAT DALAM SISTEM PELAKSANAAN TRADISI NYONGKOLAN SASAK LOMBOK - Abdul Rahim; Wisma Nugraha Christianto (Universitas Gadjah Mada, 2019)
Nyongkolan is a tradition of parading brides from the groom's home to the bride's home as the ancient Sasak noble habitus that has been crystallized into custom and implemented by all walks of Sasak society today, especially with the contemporary arts of kecimol (Cilokaq Modern Lombok) as a companion. Behind the popularity of the kecimol that is greeted enthusiastically by the community actually raises the potential for conflict. Among the most complained of congestion, eroticism, rah-rah in the streets, to conflicts with road users, residents, or fellow escort. Therefore, the indigenous consisting of Sasak nobility and religious leaders raises the discourse of banning nyongkolan using kecimol with the pretext of not according to custom, deviate from the teachings of Islam, and suggests the use of gendang beleq as a distinctive art area that became hereditary heritage. The problems arising from the ban led to contestation between the Sasak elite and the supporters of the kecimol group. How meeting point of negotiation between the repressing parties and the parties who are in the implementation of the Sasak Lombok nyongkolan tradition is studied with the perspective of Bourdieu’s social practice. The result of the negotiations raises the acceptance agreement of the kecimol as new habitus in implementation of nyongkolan tradition with the need to pay attention to order while escorting, avoiding booze and eroticism, and the use of custom symbols that reflect the Sasak identity.